PENGARUH LABA AKUNTANSI, ARUS KAS OPERASI DAN UKURAN PERUSAHAAN TERHADAP HARGA PENUTUPAN SAHAM MELALUI KEBIJAKAN DIVIDEN - Muchlis, Saiful; Setijawan, Febriani (School of Accountancy, University of Agung Podomoro, 2019)
This study aims to determine the effect of accounting profit, operating cash flow and company size onstock prices through dividend policy on consumer goods industry companies on the Indonesia StockExchange. This research uses quantitative methods and the type of explanatory research with 2016-2018 observation years in 17 company samples. The results show (1) accounting profit and operatingcash flow have a positive and significant effect on dividend policy, while the size of the company hasno influence on dividend policy. (2) accounting profit and operating cash flow do not have an effect onthe closing prices, while the size of the company has a positive and significant effect on the closingprices. (3) dividend policy has a positive and significant effect on the closing prices. (4) there is noindirect effect of dividend policy in mediating accounting profit and operating cash flow on the closingprices, but there is an indirect effect of dividend policy in mediating company size on the closing prices.